Kenya : Technical Assistance Report-Further Review of Rebased GDP Estimates. - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2022)
A Technical Assistance (TA) mission was conducted in July 2021 to review the data sources and methods used to produce revised estimates of the Kenyan National Accounts (NA) for the period 2009-2019. The mission also provided guidance on producing a revision report to be published at the time of the release.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Money and Monetary Policy